Early Inflation and Cosmology in Theories with Sub-Millimeter Dimensions - Arkani-Hamed, N; Dimopoulos, S; Kaloper, N; March-Russell, J (1999)
We discuss early cosmology in theories where the fundamental Planck mass is close to the TeV scale. In such theories the standard model fields are localized to a (3+1)-dimensional wall with n new transverse sub-millimeter sized spatial dimensions. The topic touched upon include: early inflation that occurs while the size of the new dimensions are still small, the spectrum and magnitude of density perturbations, the post-inflation era of contraction of our world while the internal dimensions evolve to their final ``large'' radius, and the production of gravitons in the bulk during these two eras. The radion moduli problem is also discussed.